1996
DOI: 10.1097/00002800-199603000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Specialization in New South Wales, Australia

Abstract: SPECIALIZATION IN NURSING is a phenomenon that occurs worldwide. In New South Wales, Australia, the positions of clinical nurse specialist (CNS) and clinical nurse consultant (CNC) were formally established only in the last decade. How these positions developed and the responses to the roles are considered in this article. In 1990/1991, we surveyed 568 specialist nurses (CNSs and CNCs) working in the Sydney metropolitan area to identify their perceptions of what they ought to be doing and what they were actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…A notable result is the data analyses' revelation that APN involvement in research remains low to non‐existent (McFadden & Miller, 1994; Appel et al ., 1996; Dawson & Benson, 1997; Dawson & McEwen, 2005; Woodward et al ., 2006; O'Baugh et al ., 2007), although research culture is generally identified as important (Jinks & Chalder, 2007), even an expectation of the APN role (Dawson & Spence, 2001). An auspicious fact regarding the research domain is the advanced practice nurse's enthusiasm and commitment to generating new evidence related to practice (Jinks & Chalder, 2007; Dawson & Coombs, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable result is the data analyses' revelation that APN involvement in research remains low to non‐existent (McFadden & Miller, 1994; Appel et al ., 1996; Dawson & Benson, 1997; Dawson & McEwen, 2005; Woodward et al ., 2006; O'Baugh et al ., 2007), although research culture is generally identified as important (Jinks & Chalder, 2007), even an expectation of the APN role (Dawson & Spence, 2001). An auspicious fact regarding the research domain is the advanced practice nurse's enthusiasm and commitment to generating new evidence related to practice (Jinks & Chalder, 2007; Dawson & Coombs, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The organizational challenges ( n = 22), rising from the newness of the APN role, lack of role clarity, healthcare system challenges, and lack of management support and recognition, were often recognized to be aggravating APN role implementation. The APN role is recognized to be still evolving (Appel et al ., 1996; Woodward et al ., 2006; Jinks & Chalder, 2007; O'Connor & Chapman, 2008), especially in the UK and Australia. In many cases, people do not know what advanced practice nurses do (McFadden & Miller, 1994; Wood et al ., 1996; Chevalier et al ., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The first APN program was introduced in New South Wales in 1990 where APNs are prepared under the work titles of CNSs (Appel, Malcolm, & Nahas, 1996) and NPs (Professional News, 1999). New South Wales has successfully established evidence and won the support of the government in introducing accreditation for these NPs (Professional News, 1999).…”
Section: Australiamentioning
confidence: 99%
“…A PhD prepared CNRC will assist in overcoming some major barriers that has an impact on a nurse’s capacity to engage in research and translate findings into clinical practice. At present, many Australian CNCs or educators have insufficient research training to conduct independent research because appointments have been based on clinical skills and experience rather than educational preparation (Appel et al. 1996).…”
Section: Discussionmentioning
confidence: 99%